Retraction: Reproductive Health Education Improves Studentsâ Knowledge on Reproductive Health: A Case Study at Universitas Respati Yogyakarta, Indonesia - Aliansi Cendekiawan Indonesia Thailand, Yayasan (Proceedings of the International Conference on Applied Science and Health, 2017)
This paper is retracted by YAYASAN ALIANSI CENDEKIAWAN INDONESIA THAILAND. The publisher has discovered that the lead author, Ni Wayan Eti Parwati, violates the caution of copyright and allegedly infringed work and copying the work of Universitas Respati Yogyakarta without permission. In YAYASAN ALIANSI CENDEKIAWAN INDONESIA THAILAND, we take seriously the value of intellectual property, thus, as the consequences of her allegations, we retract the participation of Ni Wayan Eti Parwati at the 2nd International Conference on Applied Science and Health, and all benefits appeared from the conference including recognition and publication.